A simple cytofluorimetric score may optimize testing for biallelic CEBPA mutations in patients with acute myeloid leukemia. (November 2019) - Marcolin, Riccardo; Guolo, Fabio; Minetto, Paola; Clavio, Marino; Manconi, Lorenzo; Ballerini, Filippo; Carli, Alessandro; Passannante, Monica; Colombo, Nicoletta; Carminati, Enrico; Pugliese, Girolamo; Tedone, Elisabetta; et al.
Highlights: AML with CEBPA-dm is a distinct entity with an overall favorable outcome. The evaluation of CEBPA-dm requires difficult and time consuming Sanger sequencing. CEBPA-dm AML has a peculiar immunophenotypic signature. The presence or the absence of CEBPA-dm can be predicted with our IF score. Abstract: Acute myeloid leukemia with biallelic mutation of CEBPA (CEBPA-dm AML) is a distinct good prognosis entity recognized by WHO 2016 classification. However, testing for CEBPA mutation is challenging, due to the intrinsic characteristics of the mutation itself. Indeed, molecular analysis cannot be performed with NGS technique and requires Sanger sequencing. The association of recurrent mutations or translocations with specific immunophenotypic patterns has been already reported in other AML subtypes. The aim of this study was the development of a specific cytofluorimetric score ( CEBPA-dm score), in order to distinguish patients who are unlikely to harbor the mutation. To this end, the correlation of CEBPA-dm score with the presence of the mutation was analyzed in 50 consecutive AML patients with normal karyotype and without NPM1 mutation (that is mutually exclusive with CEBPA mutation). One point each was assigned for expression of HLA DR, CD7, CD13, CD15, CD33, CD34 and one point for lack of expression of CD14. OS was not influenced by sex, age and CEBPA-dm score. Multivariate OS analysis showed that CEBPA-dm (p < 0.02) and FLT3-ITD (p < 0.01) were the strongest independent predictors of OS. With a high negative predictive value (100%), CEBPA-dm score < 6 was able to identify patients who are unlikely to have the mutation. Therefore, the application of this simple score might optimize the use of expensive and time-consuming diagnostic and prognostic assessment in the baseline work up of AML patients.